The Role Of Waqf Property Buildings For Beneficiaries - Jalaluddin; Furqani, Hafas; Ilham (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
The Tahfidzhul Quran Sulaimaniyah Habibie Center Aceh Besar Islamic Boarding School building is a temporary waqf property resulting from collaboration between the Sulaimaniyah Foundation and the Habibie Center Foundation. There are many permanent waqf building assets whose benefits are less than optimal for mauquf 'alai'ih throughout Indonesia, including in Aceh. This is because the abilities and strategies of waqf managers (nazhir) are still lacking in managing waqf assets professionally. This study aims to determine Nazir's strategy in managing and utilizing waqf land and buildings at the Sulaimaniyah Habibi Center Islamic Boarding School. The research uses a qualitative approach to sources namely Nazirs, Islamic boarding school students, Islamic boarding school alumni, village imams and local communities by collecting data using observation, interviews and documentation techniques. The data analysis method uses data reduction techniques, data presentation, and drawing conclusions. The results of the research show that Nazir's strategy in managing and utilizing waqf property buildings is by managing and utilizing ZIS (Zakat, Infaq and Alms) funds and waqf goods according to their designation as Islamic boarding school operational costs for the continuity of student learning.